The Plastic Pathfinder: A macroplastic transport and fate model for terrestrial environments - Mellink, Y.; van Emmerik, T.; Kooi, M.; Laufkötter, C.; Niemann, H. (Frontiers in Environmental Science, 2022)
Land-based plastic waste is the major source for freshwater and marine plastic pollution. Yet, the transport pathways over land remain highly uncertain. Here, we introduce a new conceptual model to forecast plastic transport on land: the Plastic Pathfinder; a numerical model that simulates the spatiotemporal distribution of macroplastic (>0.5 cm) at a river basin scale. The plastic transport driving forces are wind and surface runoff, while plastic transport is resisted by terrain surface friction. The terrain surface friction, a function of the slope and land use, is converted into thresholds that define the critical wind and surface runoff conditions required to mobilize and transport macroplastic waste. When the wind and/or surface runoff conditions exceed their respective thresholds, the model simulates the transport and (re)distribution of plastics, resulting in plastic accumulation hotspots maps and high probability transport route maps. The Plastic Pathfinder contributes to a better mechanistic understanding of plastic transport through terrestrial environments, and upon future calibration and validation, can serve as a practical tool to optimize plastic waste prevention, mitigation, and reduction strategies.